2011
DOI: 10.1155/2011/578265
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Shock Cushioning Characteristics and Vibration Transmissibility of X-PLY Corrugated Paperboard

Abstract: X-PLY corrugated paperboard is a new-type corrugated paperboard with three layers of orthotropic corrugated sandwiches structure, and may be employed to protect products from shock or vibration damage during distribution. This article deals with the characterization of properties of X-PLY corrugated paperboard relevant to its application for protective packaging in distribution, such as dynamic cushioning curves, vibration transmissibility and frequency curves. The main feature of article is the evaluation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 6 publications
(9 reference statements)
0
20
0
Order By: Relevance
“…Sek 14 and Rouillard 15 analyzed the transverse compression deformation and energy absorption of the layered corrugation structure and discovered that the corrugated paperboard was yielded to crush with the mode of layer by layer, and the gas within corrugation pores had a certain influence on the bearing capacity and energy absorption during drop shock dynamic compression. Guo and colleagues 16,17 studied the drop shock dynamic responses of honeycomb paperboard and X-PLY corrugated paperboard and indicated that these structures have excellent cushioning energy absorption. Lu et al 18 investigated the crushing mechanism and critical buckling load of honeycomb paperboard under transverse static load using sandwich plate theory.…”
Section: Introductionmentioning
confidence: 99%
“…Sek 14 and Rouillard 15 analyzed the transverse compression deformation and energy absorption of the layered corrugation structure and discovered that the corrugated paperboard was yielded to crush with the mode of layer by layer, and the gas within corrugation pores had a certain influence on the bearing capacity and energy absorption during drop shock dynamic compression. Guo and colleagues 16,17 studied the drop shock dynamic responses of honeycomb paperboard and X-PLY corrugated paperboard and indicated that these structures have excellent cushioning energy absorption. Lu et al 18 investigated the crushing mechanism and critical buckling load of honeycomb paperboard under transverse static load using sandwich plate theory.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene, as a thermoplastic constituent in TP specimens, is a contributor enhancing the damping capacity of specimen, however, it shows low stiffness values [20]. Paperboard, on the other hand, is known for its shock absorbent abilities and high damping capacities [34].…”
Section: Resultsmentioning
confidence: 99%
“…Cushioning performance, vibration transmissibility, and compressive resistance of MLCS were examined in detail in previous works (Wang, 2009;Guo et al, 2011;Kim et al, 2013;Wang et al, 2013). Guo et al (2010) considered the shape of the shock pulse of the MLCS as a half-sine wave, and they approximated the cushion curve of the peak acceleration-static stress with a third-degree poly- nomial.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that a drop height is a significant variable for dynamic cushioning performance because the position of the belly on the cushion curve shifts upward to the left with increasing drop height, while for identical drop heights, the belly shifts downward with increasing the number of layers of the MLCS. Guo et al (2011) approximated the cushion curve of X-PLY MLCS with a quadratic polynomial, and showed that the dynamic cushioning performance of X-PLY with A/F is better than that of X-PLY with B/F because the position of the belly on the cushion curve of the former is lower than that of the latter under identical drop height conditions. On the other hand, Guo and Zhang (2004) approximated the cushion curve of honeycomb paperboards with a sandwich structure, such as corrugated paperboard, with a third-degree polynomial, and reported that the position of the belly on the cushion curve shifted upward with increasing drop height shifted downward to the right with increasing material thickness under identical drop height conditions.…”
Section: Introductionmentioning
confidence: 99%